Pengaruh Variasi Waktu Fiksasi Sediaan Apus Darah Tepi (SADT) pada Pengecatan Giemsa terhadap Morfologi Sel Darah Merah - Abdul Ghofur; Tuti Suparyati; Siti Fatimah (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
The Blood Smear is a slide whose one of the surfaces is coated using a thin layer of blood and stained with painting of giemsa or wright. Before painting, the preparation is fixated with methanol (methyl alcohol). Prolonged fixation should be avoided because methanol affects subsequent painting and causes some inhibition of intracellular enzymes. Methanol that is left too long in the open air will evaporate (decrease in concentration) and contain water so that it will affect erythrocyte morphology. This study aims to find out the effect of variations in sadt fixation time on giemsa painting on the morphology of red blood cells. This type of research is an experiment. The sample numbered 30 in the form of peripheral blood smear preparations divided by 3 based on variations in fixation time of 3 minutes, 5 minutes and 10 minutes. The results of the Chi-Square statistical test obtained a signification value of 0.00 < 0.05 means that there is a significant difference in time variation in the morphological quality of cells. And the fixation time is best with a fixation time of 3 minutes, at a fixation of 5 minutes still found some crenation cells (cell grinding) with moderate criteria (<3) while fixation with a time of 10 minutes is found a lot of crenation cells (>3).